Assessment of Biofilm Formation and Hypermucoviscosity in Klebsiella oxytoca from Clinical and Community Sources - Mustaf, Haneen A.; Hafidh, Rand R.; Alsodani, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Klebsiella oxytoca is an emerging pathogen causing hospital- and community-acquired infections. Hypermucoviscous phenotype and biofilm development are considered markers of hypervirulence, causing invasive infections in healthy adults Objective: The current study aimed to evaluate the ability of K. oxytoca isolates to form biofilms and incorporate hypermucoviscous characteristics. Method: One hundred K. oxytoca isolates were collected from hospitals in the Medical City Teaching Hospital Complex, in Baghdad, Iraq. The isolates were identified by conducting manual and biochemical tests. The hypermucoviscous characteristic was analyzed by using the string test. The Congo red agar method was used to detect biofilm formation, while quantitative methods like tube adherence and microtiter plates were used to measure its strength. Statistical analysis was performed by using the SPSS Statistical package (Version 26; SPSS, IBM) and Microsoft Office Excel (2010) for drawing the figures except for the receiver operating characteristic (ROC) curve. Results: K. oxytoca was obtained from 54/100 (54%) male and 46/100 (46%) female specimens. The specimens were from inpatients 62/100 (62%), and the rest, 38/100 (38%), were from outpatients. The isolates were significantly (P = 0.0001) from urine specimens 39/100 (39%) followed by blood specimens 16/100 (16%). The string test identified 14/100 (14%) isolates as hypermucoviscous with (21.1%) being from outpatients. The biofilm was positive in 80/100 isolates. By utilizing the tube method, a strong adhesion was detected in 23/80 (28.75%) isolates. The microtiter plate method (MTP) yielded a strong biofilm in 25/80 (31.25%) isolates. The strongest biofilm was found in isolates from urine specimens (40%). Conclusion: By forming a strong biofilm and developing hypermucoviscous, the virulence potential of K. oxytoca isolates exhibited a risk to the community. Urine was considered to be the main source of the strongest biofilm-forming isolates.